Exfoliative Erythroderma: An Unusual Presentation of Paraneoplastic Pemphigus Associated with Castleman's Disease - Sirikham, Thirawut (Case Rep Dermatol, 2020)
We report a 23-year-old woman who presented with generalized scaly erythematous rash predominately on the upper trunk and hemorrhagic stomatitis. The histopathologic and immunopathologic findings were consistent with the diagnosis of paraneoplastic pemphigus. Castleman's tumor was diagnosed with computed tomography and exploratory laparotomy. A partial clinical improvement was observed after complete tumor removal and intravenous immunoglobulin administration. However, the patient died as a result of septicemia.